Introduction to Voluntary Evacuation Risk Assessment - Gromek, Pawel (Communications - Scientific letters of the University of Zilina, 2018)
Taking into consideration safety and security viewpoints of persons and property protection, evacuation as common protection mean is well known. Actually, object state-of-the-art comprises solutions generally based on experience gathered in countries much more affected by mass threats as Central Europe nationalities. Voluntary evacuation is treated as the most common evacuation form. Article presents the comparison of research conducted in USA and Poland defining voluntary evacuation scale as a significant risk factor. The evacuation risk influence determinants are described and risk assessment guidelines are performed. The guidelines are related to the state-of-the-art and the local Central Europe determinants.